Literature and literary theory in contemporary China - Zhang, Jiong, 1933- (China Perspectives, 2017)
"Marxism initiated a new era not only for people to fight for socialist future, but also for each discipline of sciences to witness profound changes. In such a context, literature, which has always been closely related to politics, will inevitably move toward a new direction. This book is composed of two parts. Part One studies the development of literary theories in contemporary China from a Marxist perspective. It introduces the basic ideas of Marxist literary theories as well as their spread and development in China, such as the combination of the theories and Chinese revolutionary literature. Moreover, it discusses the challenges facing Marxist literary theories in the 21st century under the background of diversification of literature and art, in terms of theory and practice, and high technologies which brought about electronic writing and digital communication of literary works. The second part elucidates the author's insights into major issues concerning literary theories (e.g. the relationship between literature and people, literature and reality, perception and rationality in literary creation, etc.) This book will appeal to scholars and students of literary aesthetics and Chinese literary and cultural studies. People who are interested in history of contemporary Chinese literature will also benefit from this book."--Provided by publisher.